Seasonal and macrotidal influence on the marphodynamics of estuarine beaches (Marajó island - Eastern amazon - Brazil) - Maamar, El Robrini; Silva, Paulo Victor Magno; Guereiro, Juliana Sá; Ranieri, Leilanhe Almeida (Quaternary and Environmental Geosciences, 2024)
The Marajó island situated at the mouth of the Amazon estuary, is recognized as the largest estuarine island in the world. It is surrounded by the Amazon Estuary to the west, Pará estuary to the east, the Tocantins River to the south, and the Atlantic Ocean to the north. The Pará Estuary Border of the Island is divided by the Paracauari channel, creating a division between two distinct coastlines: the coast with active cliffs and narrow beaches like Grande beach (35 m) and Joanes beach (58.4 m) located in Salvaterra. In the other side, extensive beaches such as Barra Velha beach (285 m) and Pesqueiro beach (240/300 m) with low topography and paleo mangrove terraces, located in Soure. The unique hydrodynamic conditions include tides reaching up to 5.7 m, currents of 1.7 m/s, and waves up to 1.5 m high originated from the northeast, along with average wind speeds of 7 m/s. The sedimentary equilibrium is more pronounced in the low sector. The low sector (Pesqueiro beach = 525.38 m3/m) exhibits a higher sedimentary balance compared to the high sector (Joanes beach = 250.07 m3/m and Grande beach = 88.58 m3/m). The beaches displayed an intermediate morphodynamic character, except for Grande beach (reflective/rainy season) and Joanes beach (reflective/dry). According to the RTR model, these beaches had an intermediate nature characterized by runnels and bars, except for Joanes beach (reflective/dry).